Proposta de corredores ecológicos para interligação dos Parques Estaduais de Forno Grande e Pedra Azul, ES, utilizando geotecnologias - Louzada, Franciane Lousada Rubini de Oliveira (2010)
This work had as main objective to propose routes for Ecological Corridors implantation using Geotechnologies. The specific objectives were to define the permanent preservation areas on marginal band of water courses, around springs, on slopes with declivity higher than 45 degrees and on the upper third of the hills and mountains tops; analyze the areas of use confrontation and land cover in the APPs of the surroundings of the State Parks Forno Grande and Pedra Azul - ES, from the viewpoint of Environmental Law; and to evaluate landowners predisposition regarding the acceptance of the Ecological Corridors implantation. First, 14 use classes and land cover were mapped by visual interpretation, in which the forest cover was predominant (21,349.03 ha - 41.8%), followed by pasture (14,551.35 ha - 28.4%), agriculture ( 5,032.47 ha - 9.8%) and regenerating area (3,064.38 ha - 6.0%). The predominance of forest cover shows the conservation status of the region and the importance of buffer zones of the State Parks. Following the definitions of Resolution No. 303 of CONAMA, the Permanent Preservation Areas (PPAs) were delimited which occupied approxi ately 23,453.93 ha, representing 45.9% of total area, and 35.6% of these presented misuse, especially the pasture, agriculture and reforestation with eucalyptus. Then, using the methodology of distance of less expense, six routes were proposed for implementation of the Ecological Corridor, named as Corridor "A", "B", "C", "D", "E" and "F". The best proposal was the Corridor "A", with 15,144.76 long, 1,514.48 and 2,099.57 ha in width, based on APPs images, Land Use, Slope and Confrontation of Land Use in APPs. A significant factor for choosing this corridor was the existence of large areas of vegetation and area in regeneration, the largest area of PPAs preserved and possessing great potential for tourism and agriculture. To evaluate the predisposition of landowners in accepting the implementation of the Ecological Corridors in their properties a questionnaire was applied. Only 21.8% knew what was an ecological corridor and 70.9% were interested in its implementation on their properties. According to the results, we conclude that the methodology was efficient, producing in an automated form, accurate informations about their size and spatial distribution in the landscape and development of analog and digital maps